Cytotoxicity and Antibacterial Activity of Silver Complexes Bearing Semicarbazones and Triphenylphosphine. Issue 46 (10th December 2020) - Almeida, Vitor Y. G.; Rocha, Josias S.; Felix, Débora P.; Oliveira, Gabriela P.; Lima, Mauro A.; Farias, Renan L.; Zanetti, Renan D.; Netto, Adelino V. G.; Zambom, Carolina R.; Garrido, Saulo S.; Rocha, Fillipe V.
Abstract: The present work aimed to evaluate the biological activities of the silver (I) complexes, with the formulae [Ag(L)(PPh3 )2 ] + and [Ag(L)2 ] + (L=(E)‐2‐((E)‐3‐phenylallylidene) hydrazine‐1‐carboxamide – CSC and (2E)‐2‐[(3E)‐4‐phenylbut‐3‐en‐2‐ylidene]‐hydrazinecarboxamide – BSC). Four new silver(I) compounds were synthesized and characterized by NMR 1 H, 13 C‐ 1 H, 31 P, IR, and UV‐Vis spectroscopies, molar conductivity, and elemental analysis (CNH). High cytotoxicity was found for all complexes being more active than cisplatin in the tested cell lines. The antibacterial assay demonstrated that the compounds without phosphine groups presented high levels of inhibition (80 %) at 70.4 uM against the Gram‐positive and Gram‐negative bacteria strains. The DNA interactions were investigated by UV‐Vis DNA titration, electrophoresis, and circular dichroism experiments. Data showed that the compounds did not interact with DNA in the tested conditions. However, the compounds have provided important information about the structural features that are needed in order to design new silver (I) complexes with biological activities. Abstract : Four silver compounds bearing semicarbazone and triphenylphosphine as ligands were synthesized and fully characterized. The compounds presented outstanding cytotoxicity towards prostate and breast cancer cell lines, surpass up to 16 folds the values founded to cisplatin. Further, one of the compounds acted indistinctly on the gram‐positive and gram‐negative strains. The compounds did not show any capacity to interact with the DNA molecule or supercoiled plasmid. Nonetheless, the structural features are promising to design silver coordination compounds with high antiproliferative activity.